Focused Proteomics Analysis of Habu Snake (Protobothrops flavoviridis) Venom Using Antivenom-Based Affinity Chromatography Reveals Novel Myonecrosis-Enhancing Activity of Thrombin-Like Serine Proteases - Ogawa, Tomohisa; Tobishima, Yu; Kamata, Shizuka; Matsuda, Youhei; Muramoto, Koji; Hidaka, Masafumi; Futai, Eugene; Kuraishi, Takeshi; Yokota, Shinichi; Ohno, Motonori; Hattori, Shosaku (Frontiers in Pharmacology, 2021)
Snakebites are one of the major causes of death and long-term disability in the developing countries due to the presence of various bioactive peptides and proteins in snake venom. In Japan, the venom of the habu snake (Protobothrops flavoviridis) causes severe permanent damage due to its myonecrotic toxins. Antivenom immunoglobulins are an effective therapy for snakebites, and antivenom was recently developed with effective suppressive activity against myonecrosis induced by snake venom. To compare the properties of an antivenom having anti-myonecrotic activity with those of conventional antivenom with no anti-myonecrotic activity, this study applied focused proteomics analysis of habu venom proteins using 2D gel electrophoresis. As a target protein for antivenom immunoglobulins with anti-myonecrotic activity, we identified a thrombin-like serine protease, TLSP2 (TLf2), which was an inactive proteolytic isoform due to the replacement of the active site, His43 with Arg. Additionally, we identified the unique properties and a novel synergistic function of pseudoenzyme TLf2 as a myonecrosis-enhancing factor. To our knowledge, this is the first report of a function of a catalytically inactive snake serine protease.